The lies that bind [compact disc, unabridged] : a novel - Giffin, Emily (Random House Audio, 2020)
A young woman falls hard for an impossibly perfect man before he disappears without a trace. It's two AM on a Saturday night in the spring of 2001, and twenty-eight-year-old Cecily Gardner sits alone in a dive bar on New York's Lower East Side, questioning her life. Feeling lonesome and homesick for the Midwest, she wonders if she'll ever make it as a reporter in the big city and whether she made a terrible mistake in breaking up with her longtime boyfriend, Matthew. As Cecily reaches for the phone to call him, she hears a guy on the barstool next to her say, 'Don't do it, you'll regret it.' Something tells her to listen to him, and over the next several hours, and shots of tequila, the two forges an unlikely connection. That should be it, they both decide the next morning, as Cecily reminds herself of the perils of a rebound relationship.